All signs point to Malibu [large type] - Snow, Jennifer (Thorndike Press large print top shelf., 2024)
"Hailey Harris can't stop messing with fate. A successful life coach, Hailey uses her ability to glimpse the future to guide her clients down the right path. But her gift has made her own life lonely. After all, having a real friend would mean asking someone to believe the unbelievable. The one person she might have confided in--her ex, Liam Jensen--is newly engaged to a beautiful, sweet, thoughtful heiress. But when Hailey has a vision predicting a not-so-happy ending for the couple, her mission is clear: help Liam and his fiancée avoid the biggest mistake of their lives. Stopping the wedding while planning Liam's engagement party is no easy feat. And Warren Mitchell--Liam's sexy, irritating best man and Hailey's nemesis--is suspicious of Hailey's motivations. Between sleeping with her frenemy and watching her careful plans spiral out of control, Hailey discovers the real cause of Liam's future heartbreak. But now that she knows the truth, will Hailey keep on fighting fate or trust in the love she never saw coming?" --